Cobalt / graphdiyne monolithic catalyst, preparation method thereof and application of cobalt / graphdiyne monolithic catalyst in catalytic ozonization VOCs degradation

By preparing cobalt/graphyne monolithic catalysts, the problem of high temperature and precious metal catalysts required for VOCs treatment in the prior art is solved, and VOCs are efficiently degraded at room temperature and demonstrated long-term stability.

CN119488911APending Publication Date: 2025-02-21HUAZHONG NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411581859.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The prior art has high temperature demand and easy sintering and inactivation of precious metal catalysts in the treatment of VOCs such as ethyl acetate. The treatment process for low-concentration VOCs increases operating costs and floor area.

Method used

Using a cobalt/graphyne monolithic catalyst, the single-atom cobalt/graphyne catalyst is formed by mixing, stirring and drying the graphyne and cobalt salts in a suitable solvent, and mixed with Nafion, surfactant and modifier to prepare it Honeycomb ceramic monolithic catalyst.

Benefits of technology

Highly efficient catalyzed ozonated VOCs, especially 100% degradation of ethyl acetate, methanol, propylene and toluene at room temperature, was achieved, and the catalyst exhibited high stability of 100 hours.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119488911A_ABST
    Figure CN119488911A_ABST
Patent Text Reader

Abstract

The invention discloses a cobalt / graphdiyne monolithic catalyst, a preparation method thereof and application of the cobalt / graphdiyne monolithic catalyst in catalytic ozonization VOCs degradation, and belongs to the technical field of materials. The preparation method of the cobalt / graphdiyne monolithic catalyst comprises the following steps: dispersing graphdiyne in a first solvent to obtain a dispersion liquid; dispersing cobalt salt in a second solvent to obtain a cobalt salt solution; and mixing the dispersion liquid and the cobalt salt, stirring and reacting, and then drying to obtain the cobalt / graphdiyne catalyst, and immersing a catalyst substrate material in the catalyst slurry to obtain the cobalt / graphdiyne monolithic catalyst. In addition, the invention also provides the cobalt / graphdiyne monolithic catalyst which is prepared by the preparation method. In addition, the invention also provides an application of the cobalt / graphdiyne monolithic catalyst in catalytic ozonization VOCs degradation. The cobalt / graphdiyne honeycomb ceramic monolithic catalyst provided by the invention shows extremely high VOCs adsorption performance and degradation performance in the aspect of catalyzing ozonation VOCs degradation at room temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of materials, and in particular to a cobalt / graphene monolithic catalyst and a preparation method thereof, and application thereof in catalytic ozonation degradation of VOCs. Background Art

[0002] Volatile organic compounds (VOCs) are oxygen 3 It is a common precursor of VOCs and secondary organic aerosols (SOA), which usually causes serious secondary pollution in the atmosphere and endangers human health. Ethyl acetate (hereinafter referred to as: EA), as a common industrial oxygen-containing VOCs (i.e. OVOCs), can cause environmental photochemical smog and damage the human central nervous system. Its pollution mainly comes from the industrial production and manufacturing processes of industrial spraying, packaging printing, adhesives, plastics and electronic circuits. Regarding OVOCs control technology, the most common one is catalytic oxidation technology, but this technology currently has the following main problems in the control of OVOCs such as ethyl acetate: First, the CO bond energy in ethyl acetate is difficult to build up, so a higher catalytic reaction temperature is usually required, which makes the precious metal catalyst easy to sinter and deactivate; second, the ethyl acetate control scenario is usually medium and low concentration (less than 200mg / m 3 ), so it is often necessary to cooperate with rotary adsorption, the treatment process is cumbersome and adds additional operating costs and floor space. Therefore, it is very important to find low-temperature and efficient non-precious metal catalysts and develop new low-temperature and low-concentration ethyl acetate and other VOCs treatment technologies.

[0003] How to achieve low-temperature catalytic degradation of VOCs is a technical problem that needs to be solved by existing technologies. Summary of the invention

[0004] The purpose of the present invention is to overcome the above technical deficiencies, provide a cobalt / graphene monolithic catalyst and its preparation method and application in catalytic ozonation VOCs degradation, and solve the technical problem of how to achieve low-temperature catalytic VOCs degradation in the prior art.

[0005] In order to achieve the above technical objectives, the technical solution of the present invention proposes a cobalt / graphene monolithic catalyst and a preparation method and application thereof.

[0006] The present invention provides a method for preparing a cobalt / graphene monolithic catalyst, comprising the following steps:

[0007] S1, dispersing graphyne in a first solvent to obtain a dispersion; dispersing a cobalt salt in a second solvent to obtain a cobalt salt solution;

[0008] S2, mixing the dispersion and the cobalt salt and stirring to react, and then drying to obtain the cobalt / graphene catalyst;

[0009] S3. The cobalt / graphene catalyst prepared in step S2, Nafion, a surfactant, and a modifier are mixed in a mass ratio of 1:(1-2):(5-6):(3-4) to obtain a catalyst slurry, the catalyst base material is immersed in the catalyst slurry, and then taken out and dried to obtain a cobalt / graphene monolithic catalyst.

[0010] In any embodiment, in step S1, the first solvent or the second solvent is one of methanol, anhydrous ethanol, ammonia water and water.

[0011] In any embodiment, in step S2, the cobalt salt is one or more of cobalt nitrate hexahydrate, cobalt acetate and cobalt chloride.

[0012] In any embodiment, in step S2, the stirring reaction time is 2-3 hours.

[0013] In any embodiment, in step S2, the dispersion and the cobalt salt are mixed and stirred for reaction according to a mass ratio of graphyne to cobalt salt of 10:(3-5); and / or, in step S1, the dispersion is further subjected to ultrasonic treatment for 3-5 minutes; and / or, in step S1, the cobalt salt solution is further subjected to ultrasonic treatment for 3-5 minutes.

[0014] In any embodiment, in step S3, the catalyst substrate material is one or more of honeycomb ceramics, nickel foam and copper foam.

[0015] In any embodiment, in step S3, the surfactant is one or more of polyethylene glycol, polypropylene glycol and silicone resin; and / or, in step S3, the modifier is one or both of ethylenediamine and triethylamine.

[0016] In addition, the present invention also provides a cobalt / graphene monolithic catalyst, which is prepared by the above preparation method.

[0017] In addition, the present invention also proposes a cobalt / graphene monolithic catalyst prepared by the above preparation method or the use of the above cobalt / graphene monolithic catalyst in catalytic ozonation degradation of VOCs.

[0018] In any embodiment, the VOCs are one or more of ethyl acetate, toluene, methanol and propylene.

[0019] Compared with the prior art, the invention has the following beneficial effects: the invention proposes a method for preparing a cobalt / graphite monolithic catalyst, comprising the following steps: S1, dispersing graphite in a first solvent to obtain a dispersion; dispersing a cobalt salt in a second solvent to obtain a cobalt salt solution; S2, mixing the dispersion and the cobalt salt and stirring for reaction, and then drying to obtain the cobalt / graphite catalyst; S3, mixing the cobalt / graphite catalyst obtained in step S2, Nafion, a surfactant, and a modifier according to a mass ratio of 1: (1-2): (5-6): (3-4) to obtain a catalyst slurry, immersing a catalyst substrate material in the catalyst slurry, and then taking out and drying to obtain a cobalt / graphite monolithic catalyst, and the obtained cobalt graphite honeycomb ceramic catalyst exhibits extremely high VOCs adsorption performance and degradation performance in terms of room temperature catalytic ozonation VOCs degradation. In particular, the catalyst can achieve a 100% conversion rate of ethyl acetate at room temperature (below 25°C) and a high stability of 100 hours, and can also 100% degrade methanol, propylene and toluene at room temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a scanning electron microscope image of the single-atom cobalt / graphene catalyst prepared in Example 1 of the present invention.

[0021] Figure 2 This is the Raman graph of the single-atom cobalt / graphene catalyst prepared in Example 1 of the present invention.

[0022] Figure 3 This is the XRD pattern of the single-atom cobalt / graphene catalyst prepared in Example 1 of the present invention.

[0023] Figure 4 This is the XPS graph of the single-atom cobalt / graphene catalyst prepared in Example 1 of the present invention.

[0024] Figure 5 This is a schematic diagram of the gas flow field simulation of the single-atom cobalt / graphene honeycomb ceramic catalyst model prepared in Example 1 of the present invention.

[0025] Figure 6 This is an activity curve diagram of the single-atom cobalt / graphene catalyst prepared in Example 1 of the present invention for catalyzing the ozonation degradation of ethyl acetate.

[0026] Figure 7 This is a 100-h stability diagram of the single-atom cobalt / graphene catalyst prepared in Example 1 of the present invention catalyzing the ozonation degradation of ethyl acetate.

[0027] Figure 8 The CO of the single-atom cobalt / graphene catalyst prepared in Example 1 of the present invention is x Selectivity graph; where x is either 1 or 2.

[0028] Fig. 9 This is an activity curve diagram of the single-atom cobalt / graphene honeycomb ceramic catalyst prepared in Example 1 of the present invention for catalyzing the ozonation degradation of toluene.

[0029] Fig.10 This is an activity curve diagram of the single-atom cobalt graphyne honeycomb ceramic catalyst prepared in Example 1 of the present invention for catalyzing the degradation of propylene by ozone.

[0030] Fig.11 This is an activity curve diagram of the single-atom cobalt / graphene honeycomb ceramic catalyst prepared in Example 1 of the present invention for catalyzing ozonation and methanol degradation.

[0031] Fig.12 This is an activity curve diagram of ozone degradation of the single-atom cobalt / graphene honeycomb ceramic catalyst prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0032] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0033] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0034] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0035] This specific embodiment provides a method for preparing a cobalt / graphene honeycomb ceramic monolithic catalyst, comprising the following steps:

[0036] S1. Dispersing graphyne in a first solvent to obtain a dispersion, and subjecting the dispersion to ultrasonic treatment for 3-5 minutes; dispersing a cobalt salt in a second solvent to obtain a cobalt salt solution, and subjecting the cobalt salt solution to ultrasonic treatment for 3-5 minutes; the first solvent or the second solvent is one of methanol, anhydrous ethanol, ammonia water and water;

[0037] S2. According to the mass ratio of graphyne to cobalt salt of 10:(3-5), the dispersion and the cobalt salt are mixed and stirred for reaction for 2-3 hours, and then dried at 40° C.-65° C. for more than 10 hours to obtain the cobalt / graphyne catalyst; the cobalt salt is one or more of cobalt nitrate hexahydrate, cobalt acetate and cobalt chloride.

[0038] S3. The cobalt / graphene catalyst prepared in step S2, Nafion (perfluororesin solution, a polymer dispersing adhesive), a surfactant, and a modifier are mixed in a mass ratio of 1:(1-2):(5-6):(3-4) to obtain a catalyst slurry, and the catalyst base material is immersed in the catalyst slurry, and then taken out and dried to obtain a cobalt / graphene monolithic catalyst; the catalyst base material is one or more of honeycomb ceramics, nickel foam, and copper foam; the surfactant is one or more of polyethylene glycol, polypropylene glycol, and silicone resin; and the modifier is one or both of ethylenediamine and triethylamine.

[0039] As a new type of carbon material, Graphene has a uniform pore structure and a surface high sp&sp 2 Due to its conjugated structure, easily adjustable electronic structure and large specific surface area, it is widely used as an atomic-level catalyst carrier. The coordination environment of metal cobalt and the strong metal carrier graphyne interaction make it have strong catalytic activity and selectivity for various VOCs such as ethyl acetate.

[0040] The present invention adopts an immersion stirring method and a constant temperature drying strategy to load non-precious metal atoms, thereby achieving a highly dispersed state of metal atoms cobalt on the carrier graphyne and avoiding the agglomeration of metal on the surface of the prepared graphyne catalyst.

[0041] This specific embodiment provides a cobalt / graphene monolithic catalyst, which is prepared by the above-mentioned preparation method.

[0042] In addition, this specific embodiment also proposes a cobalt / graphite monolithic catalyst prepared by the above preparation method or the above cobalt / graphite monolithic catalyst in catalytic ozonation VOCs degradation, including placing a cobalt / graphite monolithic catalyst in a reaction tube, and introducing oxygen / ozone, nitrogen and VOCs into the reaction tube; the oxygen flow rate is 30-35mL / min, the nitrogen balance gas flow rate is 10-12mL / min, and the ethyl acetate gas flow rate is 10-12mL / min, wherein the oxygen produces ozone concentration of 800-850ppm, the total gas flow rate is 50-55mL / min, and the volume space velocity is 30000-31000mLg -1 h -1 ; The temperature of the catalytic degradation is 20-30°C.

[0043] In some embodiments, the VOCs are one or more of ethyl acetate, toluene, methanol and propylene.

[0044] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0045] In the present invention, reference is made to “some embodiments”, “this embodiment”, examples, etc., which describe a subset of all possible embodiments, but it can be understood that “some embodiments” may be the same subset or different subsets of all possible embodiments and may be combined with each other without conflict.

[0046] If similar descriptions of "first / second" appear in the application documents, the following instructions are added. In the following description, the terms "first\second\third" involved are merely used to distinguish similar objects and do not represent a specific ordering of the objects. It can be understood that "first\second\third" can be interchanged in a specific order or sequence where permitted, so that the embodiments described herein can be implemented in an order other than that illustrated or described herein.

[0047] In this embodiment, the term "and / or" is merely a description of the association relationship between associated objects, indicating that three relationships may exist. For example, object A and / or object B may represent three situations: object A exists alone, object A and object B exist at the same time, and object B exists alone.

[0048] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0049] Example 1

[0050] This embodiment provides a cobalt / graphene honeycomb ceramic monolithic catalyst, which is prepared by the following steps:

[0051] Step 1: First, weigh 100 mg of gypsum powder using an analytical balance and add it to beaker A. Add a stirring magnet to beaker A, then use a 100 mL measuring cylinder to measure 20 mL of anhydrous ethanol solution and add it to beaker A. Ultrasonic dispersion is performed for 3 minutes under ultrasonic conditions to make the gypsum evenly dispersed. Finally, beaker A is transferred to a magnetic stirrer for stirring and set aside.

[0052] Step 2: First, use a 100 mL measuring cylinder to measure 20 mL of anhydrous ethanol and add it to beaker B. Then, use an analytical balance to weigh 34.5 mg of cobalt nitrate hexahydrate (Co(NO 3 ) 2 6H 2 O) was quickly added to beaker B, and finally ultrasonically dissolved for 3 min under ultrasonic conditions to fully dissolve the cobalt salt;

[0053] Step 3: Use a rubber-tipped dropper to add the cobalt nitrate hexahydrate solution in beaker B dropwise into the stirring beaker A. After fully stirring at room temperature for 2 hours, seal the mouth of beaker A with tin foil, pierce a small number of air holes with a steel needle, and then transfer to a constant temperature oven and dry at 60°C for more than 10 hours. After the anhydrous ethanol solution is fully evaporated, a dry and black single-atom cobalt graphyne catalyst sample (i.e., SA Co / Graphdiyne) is obtained.

[0054] Step 4: Prepare the catalyst slurry coated on the honeycomb ceramic substrate, which mainly includes SA Co / Graphdiyne, Nafion, polyethylene glycol, and triethylamine, and the mass ratio is 1:1:5:3. The four components are mixed to obtain the catalyst slurry. Then, the honeycomb ceramic substrate with a size of 1cm*1cm*1cm is immersed in the catalyst slurry for 10 minutes, and purged with compressed nitrogen below 2kPa for 5 minutes. The catalyst coating shedding rate is less than 7%. Finally, the honeycomb ceramic catalyst is placed in a 60°C constant temperature oven and dried for more than 3 hours to obtain a single atom cobalt / graphene honeycomb ceramic monolithic catalyst.

[0055] The single-atom cobalt graphyne catalyst sample prepared in Example 1 was subjected to the following Figure 1-2Characterization of surface structure and morphology and analysis of the surface chemical state before and after the catalyst reaction. Figure 1 It can be seen from the scanning electron microscope that the single-atom cobalt graphyne catalyst sample mainly presents irregular particle blocks without specific morphological features. Figure 2 The Raman spectrum results show that after loading the single-atom cobalt graphyne catalyst, its D-band and G-band peak positions are shifted compared to pure graphyne, proving that there is a certain interaction between the metal cobalt atoms and graphyne. Figure 3 The XRD spectrum showed no characteristic peaks of cobalt metal and its oxides, further indicating that the metallic cobalt atoms in the catalyst were highly dispersed at the atomic level without agglomeration. Figure 4 The XPS spectrum showed that the cobalt atoms on the catalyst surface existed in a divalent form, further proving the successful synthesis of the single-atom cobalt / graphene catalyst.

[0056] Figure 5 The figure is a schematic diagram of the gas flow field simulation, which proves that the airflow is well distributed inside the honeycomb ceramic.

[0057] Example 2

[0058] This embodiment provides a cobalt / graphene honeycomb ceramic monolithic catalyst, which is prepared by the following steps:

[0059] Step 1: First, weigh 100 mg of gypsum powder using an analytical balance and add it to beaker A. Add a stirring magnet to beaker A, then use a 100 mL measuring cylinder to measure 20 mL of anhydrous ethanol solution and add it to beaker A. Ultrasonic dispersion is performed for 4 minutes under ultrasonic conditions to make the gypsum evenly dispersed. Finally, beaker A is transferred to a magnetic stirrer for stirring and set aside.

[0060] Step 2: First, use a 100 mL measuring cylinder to measure 20 mL of anhydrous ethanol and add it to beaker B. Then, use an analytical balance to weigh 40 mg of cobalt nitrate hexahydrate (Co(NO 3 ) 2 6H 2 O) was quickly added to beaker B, and finally ultrasonically dissolved for 4 min under ultrasonic conditions to fully dissolve the cobalt salt;

[0061] Step 3: Use a rubber-tipped dropper to add the cobalt nitrate hexahydrate solution in beaker B dropwise into the stirring beaker A. After stirring thoroughly for 2.5 hours at room temperature, seal the mouth of beaker A with tin foil and pierce a small number of air-permeable holes with a steel needle. Then transfer to a constant temperature oven and dry at 40°C for more than 10 hours. After the anhydrous ethanol solution is fully evaporated, a dry and black single-atom cobalt graphyne catalyst sample is obtained.

[0062] Step 4 is the same as in Example 1 to obtain a cobalt / graphene honeycomb ceramic monolithic catalyst.

[0063] Example 3

[0064] This embodiment provides a cobalt / graphene honeycomb ceramic monolithic catalyst, which is prepared by the following steps:

[0065] Step 1: First, weigh 100 mg of gypsum powder using an analytical balance and add it to beaker A. Add a stirring magnet to beaker A, then use a 100 mL measuring cylinder to measure 20 mL of anhydrous ethanol solution and add it to beaker A. Ultrasonic dispersion is performed for 5 minutes under ultrasonic conditions to make the gypsum evenly dispersed. Finally, beaker A is transferred to a magnetic stirrer for stirring and set aside.

[0066] Step 2: First, use a 100 mL measuring cylinder to measure 20 mL of anhydrous ethanol and add it to beaker B. Then, use an analytical balance to weigh 42.7 mg of cobalt nitrate hexahydrate (Co(NO 3 ) 2 6H 2 O) was quickly added to beaker B, and finally ultrasonically dissolved for 5 min under ultrasonic conditions to fully dissolve the cobalt salt;

[0067] Step 3: Use a rubber-tipped dropper to add the cobalt nitrate hexahydrate solution in beaker B dropwise into the stirring beaker A. After stirring thoroughly for 3 hours at room temperature, seal the mouth of beaker A with tin foil and pierce a small number of air-permeable holes with a steel needle. Then transfer to a constant temperature oven and dry at 60°C for more than 10 hours. After the anhydrous ethanol solution is fully evaporated, a dry and black single-atom cobalt graphyne catalyst sample is obtained.

[0068] Step 4 is the same as in Example 1 to obtain a cobalt / graphene honeycomb ceramic monolithic catalyst.

[0069] Example 4

[0070] This embodiment provides a cobalt / graphene honeycomb ceramic monolithic catalyst, which is prepared by the following steps:

[0071] Step 1: First, weigh 100 mg of gypsum powder using an analytical balance and add it to beaker A. Add a stirring magnet to beaker A, then use a 100 mL measuring cylinder to measure 20 mL of anhydrous ethanol solution and add it to beaker A. Ultrasonic dispersion is performed for 3 minutes under ultrasonic conditions to make the gypsum evenly dispersed. Finally, beaker A is transferred to a magnetic stirrer for stirring and set aside.

[0072] Step 2: First, use a 100 mL measuring cylinder to measure 20 mL of anhydrous ethanol and add it to beaker B. Then, use an analytical balance to weigh 50 mg of cobalt acetate and quickly add it to beaker B. Finally, ultrasonically dissolve it for 3 minutes under ultrasonic conditions to fully dissolve the cobalt salt.

[0073] Step 3: Use a rubber-tipped dropper to add the cobalt acetate solution in beaker B dropwise into the stirring beaker A. After fully stirring at room temperature for 2 hours, seal the mouth of beaker A with tin foil and pierce a small number of air holes with a steel needle. Then transfer it to a constant temperature oven and dry it at 50°C for more than 10 hours. After the anhydrous ethanol solution is fully evaporated, a dry and black single-atom cobalt graphyne catalyst sample is obtained.

[0074] Step 4 is the same as in Example 1 to obtain a cobalt / graphene honeycomb ceramic monolithic catalyst.

[0075] Application Example 1

[0076] In order to verify the advantages of single-atom cobalt / graphene monolithic catalyst (i.e., SA Co / Graphdiyne) in the field of VOCs degradation, we applied the cobalt / graphene honeycomb ceramic monolithic catalyst prepared in Example 1, pure graphene (i.e., pureGraphdiyne) and NP Co / Graphdiyne to the room temperature catalytic ozonation decomposition activity test of ethyl acetate.

[0077] The synthesis of the NP Co / Graphdiyne comparison sample is different from that of the cobalt / graphdiyne catalyst only in the step of powder synthesis. The specific synthesis steps are as follows:

[0078] Step 1: First, weigh 100 mg of gypsum powder using an analytical balance and add it to beaker A. Add a stirring magnet to beaker A, then use a 100 mL measuring cylinder to measure 20 mL of anhydrous ethanol solution and add it to beaker A. Ultrasonic dispersion is performed for 3 minutes under ultrasonic conditions to make the gypsum evenly dispersed. Finally, beaker A is transferred to a magnetic stirrer for stirring and set aside.

[0079] Step 2: First, use a 100 mL measuring cylinder to measure 20 mL of anhydrous ethanol and add it to beaker B. Then, use an analytical balance to weigh 150 mg of cobalt phthalocyanine and quickly add it to beaker B. Finally, ultrasonically dissolve it for 3 minutes under ultrasonic conditions to fully dissolve the cobalt salt.

[0080] Step 3: Use a rubber-tipped dropper to add the cobalt phthalocyanine solution in beaker B dropwise into the stirring beaker A. After fully stirring at room temperature for 2 hours, seal the mouth of beaker A with tin foil and pierce a small number of air holes with a steel needle. Then transfer to a constant temperature oven and dry at 50°C for more than 10 hours. After the anhydrous ethanol solution is fully evaporated, a dry and black sample is obtained.

[0081] Step 4: Place the black sample in a tube furnace, heat it to 800°C at a heating rate of 10°C / min under nitrogen / argon conditions, and calcine for 90 min to obtain a nanoparticle cobalt / graphdiyne catalyst (NP Co / Graphdiyne). The nanoparticle cobalt / graphdiyne catalyst or pure graphdiyne (pure Graphdiyne) was prepared into a monolithic catalyst according to step 4 of Example 1 for the following test.

[0082] The selected test conditions are: the test gas is ethyl acetate, the gas cylinder concentration is 500ppm. The reactor is a quartz tube with an outer diameter of 22mm, an inner diameter of 20mm, and a length of 500mm. The size of the catalyst is 10mm*10mm*10mm, the oxygen flow rate is 30mL / min, the nitrogen balance gas flow rate is 10mL / min, and the ethyl acetate gas flow rate is 10mL / min. The concentration of ozone produced by oxygen is 800ppm, the total gas flow rate is 50mL / min, and the volume space velocity is 30000mLg -1 h -1 The concentration of ethyl acetate in the tail gas was detected and analyzed by gas chromatography. The reaction temperature during the test was room temperature (25°C). After the reaction was stable, the concentration of ethyl acetate at the reactor inlet and outlet was measured by chromatography, and the conversion rate was calculated according to (concentration of ethyl acetate at the reactor inlet - concentration of ethyl acetate at the reactor outlet) / (concentration of ethyl acetate at the reactor inlet) × 100%. The conditions during the 100h stability test were the same as above. Figure 6 The results show that the single-atom cobalt graphyne honeycomb ceramic catalyst can achieve 100% catalytic ozonation degradation activity of ethyl acetate at room temperature compared with other catalysts. Figure 7 The results of the catalytic stability test show that the single-atom cobalt / graphene honeycomb ceramic monolithic catalyst can achieve stable catalytic ozonation activity of ethyl acetate at room temperature for 100 hours. Figure 8 The results show that the single-atom cobalt / graphene honeycomb ceramic monolithic catalyst catalyzes the ozonation of ethyl acetate to produce CO 2 The high selectivity further proves the excellent activity of the single-atom cobalt / graphene honeycomb ceramic monolithic catalyst.

[0083] It should be noted that the catalysts prepared in Examples 2-4 have catalytic performance comparable to that of Example 1.

[0084] Application Example 2

[0085] The catalyst prepared in Example 1 was tested for room temperature catalytic ozonation decomposition activity of toluene. The selected test conditions were: the concentration of the test gas toluene in the cylinder was 500ppm. The reactor was a quartz tube with an outer diameter of 22mm, an inner diameter of 20mm, and a length of 500mm. The size of the catalyst was 10mm*10mm*10mm, the oxygen flow rate was 30mL / min, the nitrogen balance gas flow rate was 36.7mL / min, and the toluene flow rate was 33.3mL / min. The concentration of ozone produced by oxygen was 800ppm, the total gas flow rate was 100mL / min, and the volume space velocity was 30000mLg / min. -1 h -1 The reaction temperature was room temperature 25°C. After the reaction stabilized, the toluene concentrations at the reactor inlet and outlet were determined by chromatography, and the conversion rate was calculated according to (toluene concentration at the reactor inlet - toluene concentration at the reactor outlet) / (toluene concentration at the reactor inlet) × 100%. Fig. 9 The results show that the single-atom cobalt graphyne honeycomb ceramic catalyst can basically achieve complete degradation activity of toluene catalytic ozonation at room temperature.

[0086] Application Example 3

[0087] The catalyst prepared in Example 1 was tested for room temperature catalytic ozonation decomposition activity of propylene, and the selected test conditions were: the cylinder concentration of the test gas propylene was 500ppm. The reactor was a quartz tube with an outer diameter of 22mm, an inner diameter of 20mm, and a length of 500mm. The size of the catalyst was 10mm*10mm*10mm, the oxygen flow rate was 30mL / min, the nitrogen balance gas flow rate was 36.7mL / min, and the propylene flow rate was 33.3mL / min. The concentration of ozone produced by oxygen was 800ppm, the total gas flow rate was 100mL / min, and the volume space velocity was 30000mLg / min. -1 h -1 The reaction temperature was room temperature 25°C. After the reaction stabilized, the propylene concentrations at the reactor inlet and outlet were determined by chromatography, and the conversion rate was calculated according to (reactor inlet propylene concentration - reactor outlet propylene concentration) / (reactor inlet propylene concentration)×100%. Fig.10 The results show that the single-atom cobalt graphyne honeycomb ceramic catalyst can achieve 100% degradation activity of methanol catalytic ozonation at room temperature.

[0088] Application Example 4

[0089] The catalyst prepared in Example 1 was tested for room temperature catalytic ozonation decomposition activity of methanol. The selected test conditions were: the cylinder concentration of test gas methanol was 500ppm. The reactor was a quartz tube with an outer diameter of 22mm, an inner diameter of 20mm, and a length of 500mm. The size of the catalyst was 10mm*10mm*10mm, the oxygen flow rate was 30mL / min, the nitrogen balance gas flow rate was 36.7mL / min, and the methanol flow rate was 33.3mL / min. The concentration of ozone produced by oxygen was 800ppm, the total gas flow rate was 100mL / min, and the volume space velocity was 30000mLg -1 h -1 The reaction temperature was room temperature 25°C. After the reaction stabilized, the methanol concentration at the reaction outlet was measured by chromatography, and the conversion rate was calculated according to (methanol concentration at the reactor inlet - methanol concentration at the reactor outlet) / (methanol concentration at the reactor inlet) × 100%. Fig.11 The results show that single-atom cobalt graphyne honeycomb ceramic catalyst can achieve 100% degradation activity of propylene catalytic ozonation at room temperature.

[0090] Application Example 5

[0091] The catalyst prepared in Example 1 was tested for its ozone decomposition activity. The test conditions were as follows: the test gas was ozone generated by an ozone generator, and its concentration was 800ppm. The reactor was a quartz tube with an outer diameter of 22mm, an inner diameter of 220mm, and a length of 500mm. The size of the catalyst was 10mm*10mm*10mm. The oxygen flow rate was 30mL / min, the nitrogen balance gas flow rate was 10mL / min, the VOCs flow rate was 10mL / min, the total gas flow rate was 50mL / min, and the volumetric space velocity was 30000mLg -1 h -1 In order to meet the gas flow rate standard detected by the ozone analyzer, it is necessary to add another 950mL / min nitrogen gas to increase the total flow rate to 1L / min. The reaction temperature is room temperature 25°C. After the reaction is stable, the ozone concentration at the reactor inlet and outlet is measured by chromatography, and the conversion rate is calculated according to (reactor inlet ozone concentration-reactor outlet ozone concentration) / (reactor inlet ozone concentration)×100%. Fig.12 The results show that the single-atom cobalt graphyne honeycomb ceramic catalysis has an ozone activation or utilization efficiency of 40-50% at room temperature.

[0092] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing a cobalt / graphene monolithic catalyst, characterized in that: The following steps are involved: S1, dispersing graphyne in a first solvent to obtain a dispersion; dispersing a cobalt salt in a second solvent to obtain a cobalt salt solution; S2, mixing the dispersion and the cobalt salt solution, stirring and reacting, and then drying to obtain the cobalt / graphene catalyst; S3. The cobalt / graphene catalyst prepared in step S2, Nafion, a surfactant, and a modifier are mixed in a mass ratio of 1:(1-2):(5-6):(3-4) to obtain a catalyst slurry, the catalyst base material is immersed in the catalyst slurry, and then taken out and dried to obtain a cobalt / graphene monolithic catalyst.

2. The method for preparing the cobalt / graphene monolithic catalyst according to claim 1, characterized in that: In step S1, the first solvent or the second solvent is one of methanol, anhydrous ethanol, ammonia water and water.

3. The method for preparing the cobalt / graphene monolithic catalyst according to claim 1, characterized in that: In step S2, the cobalt salt is one or more of cobalt nitrate hexahydrate, cobalt acetate and cobalt chloride.

4. The method for preparing the cobalt / graphene monolithic catalyst according to claim 1, characterized in that: In step S2, the stirring reaction time is 2-3 hours.

5. The method for preparing the cobalt / graphene monolithic catalyst according to claim 1, characterized in that: In step S2, the dispersion and the cobalt salt are mixed and stirred for reaction according to a mass ratio of graphyne to cobalt salt of 10:(3-5); and / or, in step S1, the dispersion is further subjected to ultrasonic treatment for 3-5 minutes; and / or, in step S1, the cobalt salt solution is further subjected to ultrasonic treatment for 3-5 minutes.

6. The method for preparing the cobalt / graphene monolithic catalyst according to claim 1, characterized in that: In step S3, the catalyst substrate material is one or more of honeycomb ceramics, nickel foam and copper foam.

7. The method for preparing the cobalt / graphene monolithic catalyst according to claim 1, characterized in that: In step S3, the surfactant is one or more of polyethylene glycol, polypropylene glycol and silicone resin; and / or, in step S3, the modifier is one or both of ethylenediamine and triethylamine.

8. A cobalt / graphene monolithic catalyst, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the cobalt / graphene monolithic catalyst prepared by the preparation method according to any one of claims 1 to 7 or the cobalt / graphene monolithic catalyst according to claim 8 in catalytic ozonation degradation of VOCs.

10. The use according to claim 9, characterized in that: The VOCs are one or more of ethyl acetate, toluene, methanol and propylene.